Diameter growth of Zanthoxylum kellermanii P. Wilson in a tropical evergreen forest of northern Oaxaca, Mexico - Manzano-Méndez, Filemón; Valdez-Hernández, Juan Ignacio; López-López, Miguel Ángel; Vaquera-Huerta, Humberto (Instituto de Ecología, A.C., 2016)
The seasonal diameter growth of a commercially valuable tree species, Zanthoxylum kellermanii (P. Wilson), was determined. Twenty-two trees were selected in six diameter categories and dendrometric bands were used to take bimonthly growth readings. Other readings related to crown characteristics were also taken: quality (symmetry, vigor, density of foliage) and positions (light incidence). Mean annual growth in diameter fluctuated from 0,86 cm to 1,87 cm within diameter categories; from 0,52 cm to 2,04 cm within crown qualities and from 0,73 cm to 1,70 cm within crown positions. Analyses of variance showed highly significant differences (p≤0,001) among diameter categories, as well as among crown qualities and positions. Tools such as dendrometric bands along with regression models, proved to be useful to determine and project the diameter increment of the species studied.